Does philosophy cognise or convert a person? A contribution to the problem of the philosopher's "self-formation" - Radzioch, Lech (Folia Philosophica, 2003)
The present article contains a survey of selected aspect of modem philosophising that are of crucial importance for the philosopher’s “responsibility” mentioned in the title. The author points to such phenomena as the philosopher’s self-alienation being a consequence of his or her failure to carry out the initial “self-alienation”, or of its inadequacy. What is particularly emphasised is the negative influence of the currently dominant apriorism of philosophical thinking that makes it impossible for the philosopher to establish contact with the reality of existing beings. The variety of the problems touched upon by modern philosophy cannot disguise its fundamental failures originating, as it seems, among other things, from the philosophers’ insufficient sense of responsibility. The great “projects” aimed at a renewal of philosophy turned out to be impracticable because, to speak in the most general terms, their universalist envoy was incompatible with their exclusionist and individualistic essence. Oscillating between “neo-scientism” and “neo-gnosis”, the philosophical thought of the previous century was undergoing a gradual alienation, losing its original power of expressing the essential - and, at the same time, commonly realised - experiences of human life. Without attempting to provide extensive descriptions of the situation (such descriptions can be, after all, found in numerous texts devoted to “metaphilosophy”, and to historical, philosophical, and critical reflection), the author focuses on the personal “moral conditions” of the modern philosopher’s responsibility. What is meant here is also the didactic and educational aspect of philosophical reasoning, which can by treated, in a sense, as a criterion of its validity, while the possibilities of overcoming the discrepancy, which can be observed in philosophy, between “objectivity” and “axiology” has been merely hinted at.